10 Cs and its Effect on Employee Engagement – Findings among the Generation Y IT Employees from Bangalore - Dixit, Sweta; Sharma, Alka (International Journal of Psychosocial Rehabilitation, 2020)
Employee engagement has received much consideration in both research and practice due to its prospect impact on various managerial outcomes. Much has been said about employees engagement since the term was first coined in 1990 by Kahn with relatively little pragmatic evidence on the same. Findings from the present survey are expected to enrich not only the available human resource literature on the subject but also will provide baseline to policy makers while formulating employee retention policies to be celebrated by workers of Generations Y in general and in Indian IT organisations in particular. So overall it will give focus on proactive steps do leaders need to take to develop the stage of workers who are engaging in their firm? Employee engagement refers to emotional attachment of employees towards their job as well as job environment and is considered as a measurable construct. Employees from the surveyed IT companies of Bangalore were found to be highly engaged towards their organisation. The following factors came out to be important constructs among others which resulted in high score of employee’s engagement towards their organisation – Connect, Congratulate, contribute, collaborate and confidence. Gen Y is more confident as compare to other generations and have high level of expectations from their employees.